Efficacy of Withania somnifera chemotypes NMITLI – 101R, 118R and Withaferin A against experimental visceral leishmaniasis. (June 2014) - Tripathi, C. D. P.; Gupta, R.; Kushawaha, P. K.; Mandal, C.; Misra Bhattacharya, S.; Dube, A.
Summary The immunoprophylactic and therapeutic potentials of root extracts of Withania somnifera chemotypes (NMITLI‐118, NMITLI‐101) and pure withanolide–withaferin A was investigated against Leishmania donovani infection in hamsters. The naive animals, fed orally with immunostimulatory doses of chemotypes 101R, 118R (10 and 3 mg/kg) and withaferin A (9 and 3 mg/kg) for five consecutive days and challenged with Leishmania parasites on day 6, were euthanized on days 30 and 45 p.c. for the assessment of parasite clearance, real‐time analysis of mRNAs of Th1/Th2 cytokines (IFN‐γ, IL‐12, TNF‐α, iNOS/IL‐4, IL‐10 and TGF‐β), NO production, reactive oxygen species (ROS) generation, lymphocyte transformation test and antibody responses. By day 45 p.c., there was a significant increase in the mRNA expression of iNOS, IFN‐γ, IL‐12 and TNF‐α but decrease in IL‐4, IL‐10 and TGF‐β, an enhanced Leishmania‐specific LTT response as well as ROS, NO and antileishmanial IgG2 levels in 101R‐treated hamsters followed by 118R‐ and withaferin A‐treated ones, respectively. When these chemotypes were given to L. donovani‐infected hamsters at different doses, there was moderate therapeutic efficacy of chemotype 101R ( 50%) at 30 mg/kg × 5 followed by the other two. The results established that the 101R is the most potential chemotype and can be evaluated for combination therapy along with available antileishmanials.